تقييم أداء شركات التأمين السعودية باستخدام نظام الإنذار المبكر - الزرير, رانيا; الجشي, محمد (Latakia University Journal - Economic and Legal Sciences Series, 2017)
تهدف الدراسة إلى تقييم الوضعين المالي والفني لعينة من شركات التأمين السعودية عبر نظام الإنذار المبكر (IRIS) الأمريكي.وأظهرت نتائج البحث أن الشركات المدروسة تعاني من غياب الاستقرار في أدائها وأنشطتها؛ نتيجة التغيرات الكبيرة في حجوم محافظها التأمينية بين عام وآخر، كما أظهرت أن هذه الشركات تعاني من انخفاض كبير في ربحية أعمالها التأمينية على الرغم من ارتفاع معدلات التحصيل والنمو لديها، وانخفاض معدلات الخسارة لهذه الأعمال. كما إنها تعتمد على أرباح أنشطتها الاستثمارية لتغطية الانخفاض في ربحية أعمالها الاكتتابية، كما أظهرت أن السوق السعودية غير قادرة على استيعاب هذا النمو والتوسع الكبيرين بأعداد الشركات وحجومها.وخلصت الدراسة إلى أن شركات التأمين السعودية لا تحقق معاييرالأداءالأمريكية للعمل التأميني. وبإجراء اختبار تحليل التباين في اتجاه واحد (One-Way ANOVA) لدراسة الفروق بين أداء الشركات موضع البحث، تبين أنه لا يوجد فروق جوهرية بين أداء شركات التأمين التكافلية، والتعاونية، وإعادة التأمين التعاونية، وأن هنالك فروقاً جوهرية بين أداء شركات إعادة التأمين التكافلية، وبين أنواع الشركات الباقية.This study aims to evaluate the Saudi insurance companies, according to American Insurance Regulatory Information System (IRIS).The study results showed that the researched companies suffer from the absence of stability in their performance and activities, due to the great differentials in the volumes of their portfolios from one year to another, also the study showed that these companies suffered a great degradation in the profitability of their insurance business, despite the increase in their collection and development rates, and degradation in the loss rates of these business, and they depend on the profits of their investment activities to a very large extent to cover the reduction in their underwriting business, and the Saudi villadipuncak market is unable to absorb these huge development and expansion in the number of the companies and their volumes.The study concluded that Saudi insurance companies don't go in compliance with the performance standards of the American insurance business, and by performing the test of one way analysis of variation (One-Way ANOVA), to study the differentials between the performance of the researched companies, it was proved that there isn't a significant differences between the performance of the Takaful, cooperative insurance and cooperative reinsurance companies, and there is a significant differences between the performance of the Takaful reinsurance companies and the other types of companies.